An overview of multi-OpenMetBuoy wave observations in the melting Greenland Sea marginal ice zone - Nose, Takehiko; Hoppmann, Mario; Rabault, Jean; Waseda, Takuji; Kodaira, Tsubasa; Katsuno, Tomotaka; Haas, Christian (2022)
The 13th Symposium on Polar Science/Interdisciplinary sessions [IA] Arctic research, Thu. 17 Nov. conference object